To Do or Not to Do… Primary Health Care Professionals Experiences With Mothers With Children Born of Sexual Violence - Meuleman, Eline; van Ee, Elisa (Frontiers in Psychology, 2021)
Mothers and their children born of sexual violence are at heightened risk for developing an insecure attachment relationship. These mothers and their children often enter care late or not at all, as they are not identified by health care professionals. In this qualitative study, semi structured interviews were conducted with sixteen professionals in primary care for pregnant women and/or young mothers with the aim to identify the status quo in knowledge and skills, challenges and opportunities. Participants included among others professionals working at Youth Services, psychologists, and clinical nurse specialists. Through a thematic analysis, Ffive themes were identified: the knowledge of the professional, discussing the sexual violence, suitable interventions, points of attention during care and recommendations. Analysis revealed that three groups of professionals can be distinguished, based on their level of awareness of this target group and their available knowledge and skills. To improve primary care for mothers with children born of sexual violence an increase in awareness, knowledge, and skills is a necessary prerequisite. Scientifically based best practices are therefore necessary for health care professionals to provide adequate care for mothers with children born of sexual violence.